KUFR DALAM PERSPEKTIF HADIS - Abidin, Zainal (Hunafa: Jurnal Studia Islamika, 2008)
Kufr is often considered an antithesis of imân. In the mean time, imân is the fundamental part of Islamic teaching. Nevertheless, as far as the sources of Islamic teaching are concerned, the term kufr cannot  necessarily be grasped  as  disbelief in Allah (God). In  some  hadîths (the prophet’s traditions), we find some terms of kufr that do not indicate disbelief in Allâh at all. Even, some merely indicate disobedience of the Muslims in performing their Islamic teachings, such as   performing salât. Based on this, this article deals with kufr  from the hadîth perspective.Kata Kunci : kufr, perspektif hadis, dosa besar